2022
DOI: 10.3390/s22135046
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Wedge Parameters on Ultrasonic Lamb Wave Liquid-Level Sensor

Abstract: The ultrasonic Lamb wave detection principle can realize the noncontact measurement of liquid level in closed containers. When designing an ultrasonic Lamb wave sensor, it is vital to thoroughly study and select the optimal wedge size at the front of the sensor. In this paper, firstly, we select the best working mode of Lamb waves according to their propagation dispersion curve in aluminum alloy, and we obtain the best angle of wedge through experiments. Secondly, we study the impact of the size of the wedge b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 27 publications
1
1
0
Order By: Relevance
“…The non-visible modes are either non-existent or considerably less dominant relative to the appearing modes, which can be related to the perpendicular angle of incidence of the emission signal. Changing the angle of incidence by placing the transducers in an oblique orientation will shift the dominance of and generate the invisible modes in the present experiments [33,35,36]. However, our work stayed as close as possible to real applications in which normal incidence is expected.…”
Section: Resultssupporting
confidence: 51%
“…The non-visible modes are either non-existent or considerably less dominant relative to the appearing modes, which can be related to the perpendicular angle of incidence of the emission signal. Changing the angle of incidence by placing the transducers in an oblique orientation will shift the dominance of and generate the invisible modes in the present experiments [33,35,36]. However, our work stayed as close as possible to real applications in which normal incidence is expected.…”
Section: Resultssupporting
confidence: 51%
“…Gao et al [16] built a non-contact, fixed-point, liquid level monitoring system based on the ultrasonic impedance method, and studied the relationship between the length of the near-field area and the ultrasonic echo energy. Xue et al [17] studied the internal wedge parameters of the Ultrasonic Lamb Wave Liquid-Level sensor, it is indicated that the most suitable working mode as 𝐴 when 𝑓 = 3 MHz•mm and the corresponding ultrasonic incident angle is 27.39•, The wedge thickness should be as odd multiples of 1/4 wavelength. Zhao [18] provided an air-coupled ultrasonic Lamb wave liquid level detection method based on empirical mode decomposition and deep belief network for a steel oil tank of 5 mm thickness.…”
Section: Introductionmentioning
confidence: 99%